TPACK Learning in Improving Teacher Skills in Elementary School: A Systematic Literature Review - Nanola, Nouval; Maftuh, Bunyamin; Burhanudin, Burhanudin; Wulida, Yawma; Siregar, Sina Wardani (Mimbar Sekolah Dasar, 2024)
The rapid development of technology is a challenge for teachers in Indonesia in the 21 century. The pedagogical skills that only teachers have are not enough to keep up with current developments. Teachers are required to be able to collaborate with technology in their learning.   Overcoming technology challenges in education requires teachers to master competencies in content knowledge, pedagogy, and technology. The learning process with technology integration is currently known as TPACK (Technological Pedagogical Content and Knowledge). However, it was factually found that teachers' ability to integrate technology into learning still did not reach optimal levels. This study aims to identify TPACK-based learning in elementary schools, in terms of teacher ability. . This study used a systematic literature review method. One of the procedures in this research method is to analyze and interpret relevant data. Data is collected from Google Scholar. Data was searched using two keywords: "TPACK-based learning" and "primary school teacher skills". A total of 198 data articles were obtained but only 15 articles met the analysis criteria in this study. According to the findings of the analysis conducted in this study, TPACK (Technological Pedagogical and Content Knowledge) should be an essential component in the development of learning models for achieving success in today's learning activities. This is reinforced by the need for teacher training programs that aim to enhance teachers' understanding and skills in integrating TPACK into technology-based learning.